Process evaluation of electron beam irradiation-based biodegradation relevant to lignocellulose bioconversion - Bak, Jin Seop (Springer International Publishing, 2014)
In order to solve the inefficient problem of long-term biodegradation by wood-decaying fungus, rice straw (RS) was depolymerized using electron beam irradiation-based biodegradation (EBIBB). This environment-friendly program without the use of inhibitory byproducts significantly increased the digestibility and fermentability of RS. Specifically, when irradiated RS was simultaneously biodegraded by Phanerochaete chrysosporium for 10 days, the sugar yield was 65.5% of the theoretical maximum. This value was on the same level as the 64.8% (for 15 days) measured from unirradiated RS. In case of fermentability, similarly, EBIBB program had an effect on time/energy saving. Furthermore, the transcriptomic profiles under different biosystem were analyzed in order to verify possible substrate-specific regulation based on change of lignocellulosic components. Interestingly, the overall correlation based on the bias (upregulation or downregulation) was reasonably analogous, especially lignocellulolysis-related genes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2193-1801-3-487) contains supplementary material, which is available to authorized users.